Recepção de Odorico Mendes: (a)casos de crítica de tradução no séc. XIX - Vieira, Brunno Vinicius Gonçalves [UNESP] (My University, 2012)
This paper aims at gathering evidences about the reception of Odorico Mendes Greek andRoman translations among his contemporaries. Some of the most celebrated lusophone writersof the 19th Century such as Joaquim Manoel de Macedo, Gonçalves Dias and AntónioFeliciano de Castilho left us their reviews on the work of Mendes, the most productiveand controversial Brazilian translator of the time. The analysis of those data provides valuabledocuments of translation criticism that could constitute evidence of translation practices andmethods in an historical period in which Ancient Literature poetic translations were mostlyproduced.

Este artigo pretende compendiar testemunhos sobre a recepção das traduções greco-romanas de Manoel Odorico Mendes por seus contemporâneos. Alguns dos mais célebres literatos lusófonos do século XIX – entre os quais Joaquim Manoel de Macedo, Gonçalves Dias e António Feliciano de Castilho – deixaram seus comentários sobre o trabalho de Mendes, o mais produtivo e controverso tradutor brasileiro do período. O estudo desse corpus oferece registros preciosos de crítica de tradução que poderão constituir evidências de práticas e métodos tradutórios correntes em um dos períodos em que mais se produziram traduções poéticas da literatura da Antiguidade.
Odorico Mendes' reception: cases of translation criticism in 19th Century